Psychology - Weiten, Wayne (Thomson/Wadsworth, 2008)
The Seventh Edition of Wayne Weiten's popular text, PSYCHOLOGY: THEMES AND VARIATIONS, continues to offer students a unique survey of psychology with three distinct goals: to show both the unity and diversity of psychology's subject matter; to illuminate the process of research and its intimate link to application, and to make the text challenging to think about and easy to learn from